Functionalization Effect of Multi-Walled Carbon Nanotubes Used as Supports for Cu-Based Catalysts - Juan S. Morales Giurato; Matías G. Rinaudo; Maria R. Morales (Engineering Proceedings, 2025)
In this study, commercial Multi-Walled Carbon Nanotubes (MWCNTs) were subjected to two treatments: oxidation in a liquid phase using concentrated nitric acid and oxidation in a gas phase using air flow. Cu-based catalysts were prepared by ultrasound-assisted impregnation of each support in order to obtain a metal composition of 1 wt%, followed by drying and calcination under an inert atmosphere. Commercial MWCNTs without treatment were used as references. The crystalline structure of the samples was characterized by X-ray diffraction (XRD), while their textural properties were analyzed by N2 physisorption (BET). The distinctive physicochemical properties achieved in the MWCNT supports could be related to the nature of the functionalization treatment that was used, with consequent effects on the features of the Cu catalysts.